Suite de la carte réduite du Golphe de St. Laurent : contenant les costes de Labrador depuis Mecatina jusqu'a la Baye des Esquimaux, le Détroit de Belle-Isle et partie des costes de l'Isle de Terre Neuve connues sous le nom du Petit Nord - Bellin, Jacques Nicolas, 1703-1772 (Paris (France), 1753)
Black and white. Prime meridians Paris, London, the Lizard (Cornwall), Tenerife, and Ferro. North arrow with rhumb lines. Decorative title cartouche. Relief shown pictorially. Bar scale in English and French marine leagues. Shows underwater features. Includes seal of Sun-King (upper left).